The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11606-014-3076-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Views and Experiences of Interventions to Enhance the Quality of Antibiotic Prescribing for Acute Respiratory Tract Infections

Abstract: BACKGROUND: Evidence shows a high rate of unnecessary antibiotic prescriptions in primary care in Europe and the United States. Given the costs of widespread use and associated antibiotic resistance, reducing inappropriate use is a public health priority. OBJECTIVE: We aimed to explore clinicians' experiences of training in communication skills and use of a patient booklet and/or a C-reactive protein (CRP) point-of-care test to reduce antibiotic prescribing for acute respiratory tract infections (RTIs). DESIGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 30 publications
(41 reference statements)
5
73
0
1
Order By: Relevance
“…if the illness was still in its early stages and the CRP might not be initially raised) that could result in a lack of necessary antibiotic treatment 2,9,21,24…”
Section: Crp Testing For Pneumoniamentioning
confidence: 99%
“…if the illness was still in its early stages and the CRP might not be initially raised) that could result in a lack of necessary antibiotic treatment 2,9,21,24…”
Section: Crp Testing For Pneumoniamentioning
confidence: 99%
“…A study of medicine used in children in Germany recently reported that 13.8% of participants had used drugs to treat a common cold or an URTI in the previous 7 days; half of them took prescribed medications, of which antibiotics represented 11.5% 14. The reasons for antibiotic over-prescription are numerous 15,16. One of them is the difficulty in identifying children at risk of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these shortfalls clinicians working in primary care with POCT for CRP held positive views about using CRP to guide clinical decision making (Wood et al, 2011). This was further reported by Anthierens et al (2014) and Cals et al (2009b) where clinicians felt that the CRP test decreased clinical uncertainty and supported nonprescribing decisions.…”
Section: Clinicians' Perspectivesmentioning
confidence: 99%